Capacitive deionization electrode and its preparation method and application

By optimizing the combination of activated carbon and conductive agent, capacitive deionized electrodes are prepared, which solves the problems of complex electrode preparation and insufficient adsorption capacity in the prior art, and achieves efficient electrode performance and simplified production processes.

CN116135794BActive Publication Date: 2025-01-10JIANGSU UNSW CTET(YIXING) CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111368059.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-18
Publication Date
2025-01-10
Estimated Expiration
2041-11-18

AI Technical Summary

Technical Problem

The prior art When preparing capacitor deionized electrodes, the method is complicated and not suitable for large-scale production, and it is impossible to effectively improve the adsorption capacity and conductivity of the electrodes.

Method used

Using an electrode slurry containing activated carbon, conductive agent, binder and solvent, capacitive deionized electrodes are prepared by coating and drying, the specific surface area, particle size and pore size of activated carbon are optimized, and combined with an appropriate amount of conductive agent and binder ratio to form Efficient ion transport channel.

Benefits of technology

The high adsorption capacity and charging efficiency of the electrode are achieved, the preparation process is simplified, the cost is reduced, it is suitable for large-scale production, and it is safe and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116135794B_ABST
    Figure CN116135794B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a capacitor deionization electrode, comprising: mixing raw materials including activated carbon, a conductive agent, a binder and a solvent to obtain an electrode slurry; applying the electrode slurry to the surface of a current collector, and drying to obtain the capacitor deionization electrode; preferably, the mass ratio of the activated carbon to the solvent is greater than 0.2. The method of the present invention provides a method for preparing a hydrophobic electrode and a hydrophilic electrode respectively, with a simple preparation process and low preparation cost, and can prepare a capacitor deionization electrode with high yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a capacitor deionization electrode, a capacitor deionization electrode prepared by the method, and a water treatment method using the electrode. Background Art

[0002] In recent years, water shortage has become increasingly serious due to population growth and industrial development. Limited freshwater resources cannot meet the growing demand for freshwater. Therefore, desalination of brackish water and recycling of wastewater have become increasingly important in freshwater production. Various desalination technologies, including reverse osmosis and electrodialysis, have been developed, but the challenges faced by these technologies in terms of energy consumption and scale formation are particularly severe when treating groundwater brackish water.

[0003] Capacitive deionization (CDI) is a method of desalinating saline water by removing charged species (ions) from brackish water sources. In this technology, raw water passes through the spaced channels between porous carbon electrodes. During the charging phase, a low voltage potential (typically 1.2 to 1.4 volts) is applied to the electrodes, causing ions to migrate from the raw water into the pore structure of the electrodes, where they are stored within the surface-charged electrical double layer. After the electrodes eventually reach their saturated capacity for accumulating ions, they are regenerated by applying a reverse current, causing the adsorbed ions to desorb into the spaced channels and flow out as concentrated water. Therefore, no chemicals are required for electrode regeneration.

[0004] The CDI reaction device consists of many pairs of electrodes, which are separated by a screen as mentioned above, allowing water to flow between the electrode pairs. Ion exchange membranes (cation exchange membranes on the negative electrode and anion exchange membranes on the positive electrode) are placed in front of the electrodes to prevent common ion rejection and improve salt adsorption and charging efficiency.

[0005] Carbon electrodes are the main components in CDI reaction devices, and the properties of these electrodes determine the number of ions that can be adsorbed. In order to adsorb more ions during a charge-discharge cycle, the salt adsorption capacity of the electrode should be maximized.

[0006] At present, some existing technologies have disclosed carbon electrodes and preparation methods thereof. In order to improve the adsorption capacity of the electrode, the existing technologies often require complex treatment of the materials used to prepare the electrode, such as activated carbon, or coating other materials on the prepared base electrode. However, the reported methods are relatively complicated and may not be applicable to commercial applications, and there is no evidence that they can be applied to large-scale production. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing a capacitor deionization electrode with a simple preparation process, low preparation cost and suitable for large-scale production in view of at least one problem existing in the prior art.

[0008] According to a first aspect of the present invention, there is provided a method for preparing a capacitive deionization electrode, comprising:

[0009] Mixing raw materials including activated carbon, a conductive agent, a binder and a solvent to obtain an electrode slurry;

[0010] The electrode slurry is coated on the surface of the current collector and dried to prepare the capacitor deionization electrode.

[0011] In some embodiments, the mass ratio of the activated carbon to the solvent is greater than 0.2.

[0012] In some embodiments, the specific surface area of ​​the activated carbon is 800-2100 m 2 / g.

[0013] In some embodiments, the activated carbon has a particle size of 1-15 μm.

[0014] In some embodiments, the average pore size of the activated carbon is 0.5-10 nm.

[0015] In some embodiments, the activated carbon includes one or more of wood activated carbon, fruit shell activated carbon, coconut shell activated carbon and petroleum coke activated carbon.

[0016] In some embodiments, the mass ratio of the conductive agent to the activated carbon is (2-10): (75-96).

[0017] In some embodiments, the particle size of the conductive agent is 9-15 nm.

[0018] In some embodiments, the resistivity of the conductive agent is 0.05-1.50 Ωm.

[0019] In some embodiments, the conductive agent includes one or more of carbon black, acetylene black, carbon nanotubes, and graphite.

[0020] In some embodiments, the mass ratio of the binder to the activated carbon is (2-10):(75-96).

[0021] In some embodiments, the binder includes a hydrophobic binder and a hydrophilic binder.

[0022] In some embodiments, the molecular weight of the hydrophobic binder is 180,000-400,000.

[0023] In some embodiments, the hydrophobic binder includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, and polyvinyl pyrrolidone.

[0024] In some embodiments, the molecular weight of the hydrophilic binder is 25,000-205,000.

[0025] In some embodiments, the hydrophilic binder includes one or more of polyvinyl alcohol and chitosan.

[0026] In some embodiments, the raw material further comprises a thickener.

[0027] In some embodiments, the mass ratio of the thickener to the activated carbon is (1-15):(75-96).

[0028] In some embodiments, the thickener includes a polymer electrolyte, for example, one or more of polyacrylamide, polyethyleneimine, polymethacrylic acid, polyacrylic acid, and poly(4-styrenesulfonic acid).

[0029] In some embodiments, the feedstock further comprises a cross-linking agent.

[0030] In some embodiments, the molar ratio of the cross-linking agent to the binder is (0.05-0.4):1.

[0031] In some embodiments, the cross-linking agent includes one or more of glutaric acid, pentanediol, and polyvinyl butyral.

[0032] In some embodiments, the solvent includes an organic solvent and / or an inorganic solvent, for example, one or more of 1-methyl-2-pyrrolidone, dimethylacetamide, ethanol, water and acetic acid.

[0033] In some embodiments, the method comprises the steps of:

[0034] dissolving the binder in the solvent;

[0035] optionally adding a thickener and / or a cross-linking agent;

[0036] Adding the activated carbon and the conductive agent, and mixing to obtain the electrode slurry;

[0037] The electrode slurry is coated on the surface of the current collector and dried to prepare the capacitor deionization electrode.

[0038] According to a second aspect of the present invention, there is provided a capacitor deionization electrode, which is prepared by the method described in the first aspect of the present invention.

[0039] According to some embodiments of the present invention, a capacitor deionization electrode is provided, which includes a current collector and an active layer coated on the surface of the current collector, wherein the active layer includes activated carbon, a conductive agent and a binder.

[0040] According to some embodiments of the present invention, a capacitor deionization electrode is provided, which includes a current collector and an active layer coated on the surface of the current collector, wherein the active layer includes activated carbon, a conductive agent, a binder and a thickener.

[0041] According to some embodiments of the present invention, a capacitor deionization electrode is provided, which includes a current collector and an active layer coated on the surface of the current collector, wherein the active layer includes activated carbon, a conductive agent, and a cross-linked binder.

[0042] According to some embodiments of the present invention, a capacitor deionization electrode is provided, which includes a current collector and an active layer coated on the surface of the current collector, wherein the active layer includes activated carbon, a conductive agent, a cross-linked binder and a thickener.

[0043] According to a third aspect of the present invention, a capacitive deionization reactor is provided, which comprises the capacitive deionization electrode according to the second aspect of the present invention.

[0044] According to a fourth aspect of the present invention, there is provided a water treatment method, comprising treating water using the capacitive deionization electrode described in the second aspect of the present invention or the capacitive deionization reactor described in the third aspect of the present invention.

[0045] In some embodiments, the water treatment includes seawater desalination, wastewater purification, high-purity water preparation, industrial and agricultural water desalination, or domestic water desalination. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 Schematic diagram of a capacitive deionization reactor according to one embodiment of the present invention.

[0047] Figure 2 The relationship between the conductivity and concentration of the NaCl solution calibrated before the experiment to test the adsorption capacity (SAC) and charge efficiency (CE) of the electrode.

[0048] Figure 3 This is a graph showing the adsorption capacity and charging efficiency test results of the electrodes prepared in Examples 1-6 of the present invention.

[0049] Figure 4 This is a graph showing the adsorption capacity and charging efficiency test results of the electrodes prepared in Examples 11-15 of the present invention.

[0050] Figure 5 This is a graph showing the adsorption capacity and charging efficiency test results of the electrodes prepared in Examples 16-21 of the present invention.

[0051] Figure 6 This is a graph showing the adsorption capacity and charging efficiency test results of the electrodes prepared in Examples 22-25 of the present invention.

[0052] Figure 7 This is a graph showing the adsorption capacity and charging efficiency test results of the electrodes prepared in Examples 26-29 of the present invention.

[0053] Figure 8 This is a graph showing the adsorption capacity and charging efficiency test results of the electrodes prepared in Examples 17 and 30 of the present invention.

[0054] Fig. 9 This is a graph showing the test results of the adsorption capacity and charging efficiency of the electrodes prepared in Examples 30-33 of the present invention.

[0055] Fig.10 This is a graph showing the adsorption capacity and charging efficiency test results of the electrodes prepared in Examples 30 and 34 of the present invention.

[0056] Fig.11 This is a graph showing the adsorption capacity and charging efficiency test results of the electrodes prepared in Examples 34-39 of the present invention. DETAILED DESCRIPTION

[0057] definition

[0058] References in the specification to "one embodiment", "preferred embodiment", "exemplary embodiment", etc., mean that the described embodiment may include specific features, structures, or characteristics, but not every embodiment may include specific features, structures, or characteristics. Moreover, such phrases do not necessarily refer to the same embodiment. In addition, when a specific feature, structure, or characteristic is described in conjunction with an embodiment, whether or not it is explicitly described, it is deemed that the effect of applying the feature, structure, or characteristic to other embodiments is within the knowledge of those skilled in the art.

[0059] Any numerical value mentioned in the present invention includes all values ​​that increase by one unit each time from the lowest value to the highest value if there is only an interval of two units between any minimum value and any maximum value. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, time, etc. is declared to be 50-90, in this specification it means that 51-89, 52-88... and 69-71 and 70-71 are specifically listed. For non-integer values, 0.1, 0.01, 0.001 or 0.0001 can be appropriately considered as a unit. These are just some specially specified examples. In this application, in a similar manner, all possible combinations of numerical values ​​between the listed lowest and highest values ​​are considered to have been disclosed.

[0060] As used herein, unless otherwise specified, the term "a / kind" is used to include one / kind or more / kinds, and the term "or" is used to represent a non-exclusive "or". In addition, when the terms used herein are not otherwise defined, they should be understood to be used for descriptive purposes only and not for limiting purposes. In addition, all publications, patents, and patent documents mentioned in the specification are incorporated herein by reference in their entirety, just as if they were separately incorporated by reference. If there is a discrepancy between the usage of this document and those documents incorporated by reference, the usage in the cited references should be considered to supplement this document. For irreconcilable inconsistencies, the usage in this article shall prevail.

[0061] In the manufacturing method described in the specification, except for the explicit description of the time or operation sequence, the steps can be implemented in any order without departing from the principles of the present invention. The claim indicates that one step is implemented first, and then several other steps are implemented. It should be considered that the first step is implemented before any other step, and the other steps can be performed in any other step unless the order is further listed in the step in the other step. For example, a claim stating "step A, step B, step C, step D, and step E" should be interpreted to mean that step A is implemented first, step E is implemented last, and steps B, C, and D are implemented in steps A and E. They can be performed in any order, and these orders still fall within the literal scope of the process claimed for protection by the claims. Similarly, given steps or sub-steps can be repeated.

[0062] References to "electrode" in the specification refer to "capacitive deionization electrode" and "reactor" refer to "capacitive deionization reactor" unless otherwise indicated by the context.

[0063] Method for preparing capacitive deionization electrode

[0064] In some embodiments, the present invention provides a method for preparing a capacitive deionization electrode, comprising:

[0065] Mixing raw materials including activated carbon, a conductive agent, a binder and a solvent to obtain an electrode slurry;

[0066] The electrode slurry is coated on the surface of the current collector, and after drying, the capacitor deionization electrode is prepared;

[0067] Preferably, the mass ratio of the activated carbon to the solvent is 0.2 or more.

[0068] In some embodiments, the mass ratio of the activated carbon to the solvent is 0.2-0.5, for example, 0.25, 0.3, 0.35, 0.4, 0.45 and any value therebetween.

[0069] In some embodiments, the mass ratio of the activated carbon to the solvent is 0.2-0.34.

[0070] In some embodiments, the specific surface area of ​​the activated carbon is 800-2100 m 2 / g, for example, 800m 2 / g, 850m 2 / g、900m 2 / g, 950m 2 / g、1000m 2 / g, 1050m 2 / g、1100m 2 / g, 1150m 2 / g、1200m 2 / g, 1250m 2 / g、1300m 2 / g, 1350m 2 / g、1400m 2 / g, 1450m 2 / g、1500m 2 / g, 1550m 2 / g、1600m 2 / g, 1650m 2 / g、1700m 2 / g, 1750m 2 / g、1800m 2 / g, 1850m 2 / g、1900m 2 / g, 1950m 2 / g, 2000m 2 / g, 2050m 2 / g and any value in between.

[0071] In some embodiments, the specific surface area of ​​the activated carbon is 800-1800 m 2 / g

[0072] In some embodiments, the specific surface area of ​​the activated carbon is 800-1700 m 2 / g.

[0073] In some embodiments, the specific surface area of ​​the activated carbon is 1600-1700 m 2 / g.

[0074] In some embodiments, the particle size of the activated carbon is 1-18 μm, for example, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm, 15 μm, 16 μm, 17 μm and any value therebetween.

[0075] In some embodiments, the particle size of the activated carbon is 5-15 μm.

[0076] In some embodiments, the average pore size of the activated carbon is 0.5-10 nm, for example, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 5.5 nm, 6 nm, 6.5 nm, 7 nm, 7.5 nm, 8 nm, 8.5 nm, 9 nm, 9.5 nm and any value therebetween.

[0077] In some embodiments, the average pore size of the activated carbon is less than 5 nm.

[0078] In some embodiments, the average pore size of the activated carbon is less than 2 nm.

[0079] In some embodiments, the average pore size of the activated carbon is 0.5-2 nm.

[0080] In some embodiments, the average pore size is calculated by dividing the pore volume by the specific surface area.

[0081] As the main material of the electrode, the properties of activated carbon have a great influence on the performance of the electrode. Some prior arts mention the preparation and activation methods of activated carbon for capacitive deionization technology. However, the reported methods are relatively complicated and may not be applicable to commercial applications, and there is no evidence that they can be applied to large-scale production.

[0082] The inventors have found that the activated carbon with the above parameters has a better adsorption capacity, can form an effective ion transmission channel, and is conducive to the diffusion of ions into the double electric layer of the micropores, thereby eliminating the need for further activation methods of the activated carbon.

[0083] In some embodiments, the activated carbon is not chemically modified.

[0084] In some embodiments, the activated carbon is not acid-modified, such as phosphoric acid-modified.

[0085] In some embodiments, the activated carbon is phosphorus-free.

[0086] In some embodiments, the activated carbon includes one or more of wood activated carbon, fruit shell activated carbon, coconut shell activated carbon and petroleum coke activated carbon.

[0087] In some embodiments, the activated carbon is petroleum coke activated carbon, fruit shell activated carbon or coconut shell activated carbon, with a specific surface area of ​​800-1700m 2 / g, and the average pore size is 0.5-2nm.

[0088] In some embodiments, the activated carbon is petroleum coke activated carbon or coconut shell activated carbon, with a specific surface area of ​​1600-1700m 2 / g, and the average pore size is 0.5-1.5nm.

[0089] In some embodiments, the amount of activated carbon used accounts for 75%-96% of the total mass of the electrode.

[0090] In some embodiments, the total mass of the electrode refers to the total mass of other ingredients except the solvent and the cross-linking agent when preparing the electrode slurry, and the other ingredients include, for example, activated carbon, a conductive agent, a binder, and an optional thickener.

[0091] In some embodiments, the particle size of the conductive agent is 8-15 nm, for example, 8.5 nm, 9 nm, 9.5 nm, 10 nm, 10.5 nm, 11 nm, 11.5 nm, 12 nm, 12.5 nm, 13 nm, 13.5 nm, 14 nm, 14.5 nm and any value therebetween.

[0092] In some embodiments, the resistivity of the conductive agent is 0.05-1.50Ωm, for example, 0.1Ωm, 0.15Ωm, 0.2Ωm, 0.25Ωm, 0.3Ωm, 0.35Ωm, 0.4Ωm, 0.45Ωm, 0.5Ωm, 0.55Ωm, 0.6Ωm, 0.65Ωm, 0.7Ωm, 0.75Ωm, 0.8Ωm, 0.85Ωm, 0.9Ωm, 0.95Ωm, 1Ωm, 1.05Ωm, 1.1Ωm, 1.15Ωm, 1.2Ωm, 1.25Ωm, 1.3Ωm, 1.35Ωm, 1.4Ωm, 1.45Ωm and any value therebetween.

[0093] In some embodiments, the conductive agent includes one or more of carbon black, acetylene black, carbon nanotubes, and graphite.

[0094] In some embodiments, the conductive agent is carbon black, and its particle size is 9-11 nm.

[0095] Since the porous structure of activated carbon reduces its conductivity, adding a small amount of conductive agent can increase the conductivity of the electrode. The inventors found that the conductive agent with the above particle size range is more conducive to its dispersion in the electrode and connects the activated carbon particles.

[0096] In some embodiments, the amount of the conductive agent is 2%-10% of the total mass of the electrode.

[0097] In some embodiments, the mass ratio of the conductive agent to the activated carbon is (2-10):(75-96), for example, (3-9):(80-95).

[0098] The inventors have found that limiting the amount of the conductive agent to the above range can maximize the ion adsorption capacity while improving the electrode conductivity.

[0099] In some embodiments, the binder includes a hydrophobic binder and a hydrophilic binder.

[0100] In some embodiments, the molecular weight of the hydrophobic binder is 180,000-400,000.

[0101] In some embodiments, the hydrophobic binder includes one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), and polyvinylpyrrolidone (PVP).

[0102] In some embodiments, the molecular weight of the hydrophilic binder is 25,000-205,000, such as 27,000-67,000, such as 27,000-47,000.

[0103] In some embodiments, the hydrophilic binder includes one or more of polyvinyl alcohol (PVA) and chitosan (CS).

[0104] In the field of fuel cells or supercapacitors, hydrophobic binders are often used to prepare carbon electrodes. The inventors unexpectedly discovered that in capacitive deionization technology, the use of hydrophilic electrodes is more conducive to water entering the electrodes and ion migration. In addition, the use of hydrophilic binders can avoid the use of toxic organic solvents, and the preparation method is safer and more environmentally friendly.

[0105] The main function of the binder is to bind the electrode material and to bind the electrode material to the current collector. The higher the molecular weight of the binder, the greater the viscosity of the slurry prepared, which is more conducive to thickness control during the coating process; however, the high molecular weight binder is easy to entangle together due to its long molecular chain, thus blocking the carbon pores used for ion adsorption. The present invention has found that the use of a binder with the above molecular weight can obtain the best coating performance without blocking the carbon pores, which is more conducive to its dispersion in the electrode.

[0106] In some embodiments, the amount of the binder is 2%-10% of the total mass of the electrode.

[0107] In some embodiments, the amount of the binder is 2-6%, such as 3-4%, based on the weight of the electrode.

[0108] Too much binder will block the carbon pores, while too little binder will reduce the mechanical properties of the electrode and cause carbon powder to fall off the electrode. The inventors have found that when the amount of binder is within the above range, the prepared electrode has good salt adsorption capacity and electrode charge efficiency.

[0109] In some embodiments, the mass ratio of the binder to the activated carbon is (2-10):(75-98), for example, (2-10):(75-96), for example, (2-9):(80-90).

[0110] In some embodiments, the raw material further comprises a thickener.

[0111] In some embodiments, when a hydrophilic binder is employed, a thickener is used.

[0112] When a hydrophilic binder is used, since the viscosity of water is much lower than that of an organic solvent and the amount of binder used is very small, the thinner electrode slurry prepared with the hydrophilic binder will be unfavorable for electrode coating and electrode thickness control. Therefore, using a small amount of thickener can increase the viscosity of the electrode slurry.

[0113] In some embodiments, the thickener comprises a polymer electrolyte thickener.

[0114] In some specific embodiments, the polymer electrolyte includes a positively charged polymer electrolyte and / or a negatively charged polymer electrolyte.

[0115] The use of charged polymer electrolyte thickeners can not only increase the viscosity of the electrode slurry, but also improve the ion transport capacity of the electrode, thereby improving the electrode performance.

[0116] In some specific embodiments, the thickener includes one or more of polyacrylamide, polyethyleneimine, polymethacrylic acid, polyacrylic acid, and poly(4-styrenesulfonic acid).

[0117] In some specific embodiments, the thickener comprises polyethyleneimine and / or polyacrylic acid.

[0118] In some embodiments, the amount of the thickener is 1%-15% of the total mass of the electrode.

[0119] In some embodiments, the amount of the thickener is 3%-10% of the total mass of the electrode.

[0120] In some embodiments, the mass ratio of the thickener to the activated carbon is (1-15):(75-96), for example, (3-10):(80-95).

[0121] In some embodiments, the feedstock further comprises a cross-linking agent.

[0122] In some embodiments, when a hydrophilic binder is employed, a cross-linking agent is used.

[0123] When a hydrophilic binder is used, the hydrophilic binder is usually easily soluble in water. In order to prevent the binder from dissolving out of the electrode, an appropriate amount of a cross-linking agent may be added to reduce the solubility of the binder in water.

[0124] In some embodiments, the molar ratio of the crosslinking agent to the binder is (0.05-0.4):1, for example, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.35:1 and any value therebetween.

[0125] In some embodiments, the molar ratio of the cross-linking agent to the binder is (0.1-0.4):1, for example, 0.2:1.

[0126] In some embodiments, the cross-linking agent includes one or more of glutaric acid, pentanediol, and polyvinyl butyral.

[0127] In some embodiments, the solvent includes an organic solvent and / or an inorganic solvent.

[0128] In some specific embodiments, the solvent includes one or more of 1-methyl-2-pyrrolidone (NMP), dimethylacetamide, ethanol, water and acetic acid.

[0129] In some embodiments, when a hydrophobic binder is used, an organic solvent is used.

[0130] In some embodiments, the method for preparing a capacitive deionization electrode comprises the following steps:

[0131] dissolving the binder in the solvent;

[0132] optionally adding a thickener and / or a cross-linking agent;

[0133] Adding the activated carbon and the conductive agent, and mixing to obtain the electrode slurry;

[0134] The electrode slurry is coated on the surface of the current collector and dried to prepare the capacitor deionization electrode.

[0135] In some embodiments, during the process of forming the electrode slurry, the binder, optional thickener, optional cross-linking agent, activated carbon and conductive agent may be dissolved in the solvent by heating, stirring, etc. to obtain the electrode slurry. The stirring time is not particularly limited and may be determined according to the actual dissolution conditions, for example, 3-4 hours.

[0136] In some embodiments, the electrode slurry may be prepared by the following steps:

[0137] The hydrophobic binder is added to the organic solvent and stirred for a period of time, such as 4 hours, so that the binder is completely dissolved in the organic solvent. Activated carbon and a conductive agent are added and uniformly mixed in the solvent to form an electrode slurry.

[0138] In some embodiments, the electrode slurry may be prepared by the following steps:

[0139] Dissolve the hydrophilic binder in a solvent (e.g., deionized water or 2.5% acetic acid solution) under heating (heating temperature is, for example, 90°C), stir for a period of time, for example, 4 hours, and add a certain amount of crosslinking agent after the binder is completely dissolved. If the viscosity of the slurry needs to be increased, a small amount of thickener can be added. Add activated carbon and conductive agent, and mix the activated carbon and conductive agent evenly in the solvent to form an electrode slurry.

[0140] In some embodiments, the present invention does not specifically limit the manner of coating the electrode slurry on the surface of the current collector, and those skilled in the art may choose by themselves, for example, the electrode slurry may be coated on the current collector with a certain thickness, such as 350-1000 μm, by using a scraper.

[0141] In some embodiments, the blade thickness is adjusted so that the thickness of the coated electrode slurry is 350-900 μm, for example, 600-900 μm.

[0142] In some embodiments, after the electrode slurry is coated on the surface of the current collector, it is dried to prepare the capacitor deionization electrode.

[0143] In some embodiments, the drying temperature is 90-150° C. and the drying time is 10-20 h.

[0144] Drying can not only evaporate the solvent in the slurry, but also allow the binder and the cross-linking agent to undergo a sufficient cross-linking reaction.

[0145] In some embodiments, a method for preparing a capacitive deionization electrode is provided:

[0146] Dissolving a hydrophobic binder in a solvent, wherein the amount of the binder accounts for 2-6% of the total mass of the electrode;

[0147] Add activated carbon, wherein the activated carbon is petroleum coke activated carbon, fruit shell activated carbon or coconut shell activated carbon, with a specific surface area of ​​800-1700m 2 / g, average pore size is 0.5-2nm;

[0148] Adding conductive agent carbon black, the particle size of which is 9-11 nm, and mixing to obtain electrode slurry;

[0149] The obtained electrode slurry is coated on the surface of the current collector with a thickness of 350-900 μm by using a scraper, and a capacitor deionization electrode is prepared after drying.

[0150] In some embodiments, a method for preparing a capacitive deionization electrode is provided:

[0151] Dissolving a hydrophobic binder in a solvent, wherein the amount of the binder accounts for 3-4% of the total mass of the electrode;

[0152] Add activated carbon, where the activated carbon is petroleum coke activated carbon or coconut shell activated carbon, with a specific surface area of ​​1600-1700m 2 / g, average pore size is 0.5-1.5nm;

[0153] Adding conductive agent carbon black, the particle size of which is 9-11 nm, and mixing to obtain electrode slurry;

[0154] The obtained electrode slurry is coated on the surface of the current collector with a thickness of 600-900 μm by using a scraper, and a capacitor deionization electrode is prepared after drying.

[0155] In some embodiments, a method for preparing a capacitive deionization electrode is provided:

[0156] Dissolving a hydrophilic binder in a solvent, wherein the molecular weight of the binder is 25000-205000;

[0157] Adding a crosslinking agent, wherein the molar ratio of the crosslinking agent to the binder is (0.1-0.4):1;

[0158] Add activated carbon, wherein the activated carbon is petroleum coke activated carbon, fruit shell activated carbon or coconut shell activated carbon, with a specific surface area of ​​800-1700m 2 / g, average pore size is 0.5-2nm;

[0159] Adding conductive agent carbon black, the particle size of which is 9-11 nm, and mixing to obtain electrode slurry;

[0160] The obtained electrode slurry is coated on the surface of the current collector with a thickness of 650-1000 μm by using a scraper, and a capacitor deionization electrode is prepared after drying.

[0161] In some embodiments, a method for preparing a capacitive deionization electrode is provided:

[0162] Dissolving a hydrophilic binder in a solvent, wherein the molecular weight of the binder is 25000-205000;

[0163] Add thickener, the amount of thickener accounts for 3-10% of the total mass of the electrode;

[0164] Add activated carbon, wherein the activated carbon is petroleum coke activated carbon, fruit shell activated carbon or coconut shell activated carbon, with a specific surface area of ​​800-1700m 2 / g, average pore size is 0.5-2nm;

[0165] Adding conductive agent carbon black, the particle size of which is 9-11 nm, and mixing to obtain electrode slurry;

[0166] The obtained electrode slurry is coated on the surface of the current collector with a thickness of 650-1000 μm by using a scraper, and a capacitor deionization electrode is prepared after drying.

[0167] In some embodiments, a method for preparing a capacitive deionization electrode is provided:

[0168] Dissolving a hydrophilic binder in a solvent, wherein the molecular weight of the binder is 25000-205000;

[0169] Adding a crosslinking agent, wherein the molar ratio of the crosslinking agent to the binder is (0.1-0.4):1;

[0170] Add thickener, the amount of thickener accounts for 3-10% of the total mass of the electrode;

[0171] Add activated carbon, wherein the activated carbon is petroleum coke activated carbon, fruit shell activated carbon or coconut shell activated carbon, with a specific surface area of ​​800-1700m 2 / g, average pore size is 0.5-2nm;

[0172] Adding conductive agent carbon black, the particle size of which is 9-11 nm, and mixing to obtain electrode slurry;

[0173] The obtained electrode slurry is coated on the surface of the current collector with a thickness of 650-1000 μm by using a scraper, and a capacitor deionization electrode is prepared after drying.

[0174] In some embodiments, a method for preparing a capacitive deionization electrode is provided:

[0175] Dissolving a hydrophilic binder in a solvent, wherein the molecular weight of the binder is 25000-205000;

[0176] Adding a crosslinking agent, wherein the molar ratio of the crosslinking agent to the binder is 0.2:1;

[0177] Adding a thickener, wherein the thickener is a polymer electrolyte thickener, and the amount of the thickener accounts for 3% of the total mass of the electrode;

[0178] Add activated carbon, wherein the activated carbon is petroleum coke activated carbon, fruit shell activated carbon or coconut shell activated carbon, with a specific surface area of ​​800-1700m 2 / g, average pore size is 0.5-2nm;

[0179] Adding conductive agent carbon black, the particle size of which is 9-11 nm, and mixing to obtain electrode slurry;

[0180] The obtained electrode slurry is coated on the surface of the current collector with a thickness of 650-900 μm by using a scraper, and a capacitor deionization electrode is prepared after drying.

[0181] Capacitive deionization electrode

[0182] In some embodiments, the present invention provides a capacitor deionization electrode, which is prepared by the above method of the present invention.

[0183] In some embodiments, the capacitor deionization electrode includes a current collector and an active layer coated on the surface of the current collector, and the active layer includes activated carbon, a conductive agent, and a binder.

[0184] In some embodiments, the present invention provides a capacitor deionization electrode, which includes a current collector and an active layer coated on the surface of the current collector, wherein the active layer includes activated carbon, a conductive agent, a binder, and a thickener.

[0185] In some embodiments, the present invention provides a capacitor deionization electrode, which includes a current collector and an active layer coated on the surface of the current collector, wherein the active layer includes activated carbon, a conductive agent, and a cross-linked binder.

[0186] In some embodiments, the present invention provides a capacitor deionization electrode, which includes a current collector and an active layer coated on the surface of the current collector, wherein the active layer includes activated carbon, a conductive agent, a thickener, and a cross-linked binder.

[0187] In some embodiments, the thickness of the active layer is 250-900 μm, for example, 250-600 μm, for example, 500-800 μm.

[0188] Capacitive deionization reactor

[0189] In some embodiments, the present invention provides a capacitive deionization reactor comprising any one of the capacitive deionization electrodes described in the present invention.

[0190] In some embodiments, the capacitive deionization reactor comprises a shell and at least one pair of capacitive deionization electrodes according to the present invention disposed therein.

[0191] In some embodiments, the positive electrode and the negative electrode in the at least one pair of electrodes may be the same as or different from each other.

[0192] In some embodiments, a certain voltage is applied between each pair of electrodes to form an electrostatic field.

[0193] In some embodiments, the electrodes are separated by a mesh to allow water to flow between the electrode pairs.

[0194] In some embodiments, an ion exchange membrane is placed before the electrode. For example, a cation exchange membrane is placed before one of at least one pair of electrodes, and an anion exchange membrane is placed before the other to prevent common ion rejection and improve salt adsorption and charging efficiency.

[0195] In some embodiments, the capacitive deionization reactor is assembled from a housing, a capacitive deionization electrode, an ion exchange membrane, a spacer and a sealing gasket. Such a capacitive deionization reactor is also called a membrane capacitive deionization reactor (MCDI).

[0196] Figure 1 Schematic diagram of a capacitive deionization reactor according to one embodiment of the present invention, which is assembled from an acrylic plate (with water inlet and outlet holes), electrodes, an ion exchange membrane, a nylon spacer and a rubber sealing gasket.

[0197] Water treatment methods

[0198] In some embodiments, the present invention provides a method for treating water, comprising treating water using any one of the capacitive deionization electrodes described in the present invention or the capacitive deionization reactor described in the present invention.

[0199] In some embodiments, the water treatment includes seawater desalination, wastewater purification, high-purity water preparation, industrial and agricultural water desalination, or domestic water desalination.

[0200] In some embodiments, wastewater to be treated is introduced into the capacitive deionization reactor of the present invention, voltage is applied, ions in the wastewater migrate into the pore structure of the electrode, and purified water flows out of the capacitive deionization reactor.

[0201] In some embodiments, after the electrode reaches the saturation capacity of its ability to accumulate ions, the electrode is regenerated by applying a reverse current.

[0202] Example

[0203] The present invention is further described below through specific examples.

[0204] The adsorption capacity (SAC) and charge efficiency (CE) of the electrode prepared in the embodiment were measured by the following method:

[0205] The capacitive deionization electrodes prepared in the examples were used as electrode materials for membrane capacitive deionization devices (5.8×5.8 cm 2 ), and assembled with acrylic plate (with water inlet and outlet holes), ion exchange membrane, nylon spacer and rubber sealing gasket into a membrane capacitive deionization device (MCDI device), such as Figure 1 shown.

[0206] At a flow rate of 19 mL / min, a peristaltic pump was used to flush NaCl solution (concentration of 1000 mg / L or 2000 mg / L) into the MCDI device, and the effluent was collected in a beaker, and the conductivity of the effluent was monitored in real time using a conductivity meter. The voltage test range between the electrode materials was 0-1.4 V, and the current density applied to the electrodes by an electrochemical workstation was 2 mA / cm 2 .

[0207] The relationship between the conductivity and concentration of the NaCl solution calibrated before the experiment is as follows: Figure 2 As shown in the figure, we can see that c = 0.5236x, R 2 = 0.9999, where x is the conductivity of the NaCl solution (μS / cm), c is the concentration of the NaCl solution (mg / L), and R 2 is the variance.

[0208] According to the relationship between solution conductivity and concentration calibrated before the experiment, the change in conductivity is used to obtain the change in concentration; according to the input current and charging time, the input charge is obtained, and the adsorption capacity (SAC) and charging efficiency (CE) of the electrode are calculated according to the following formula:

[0209]

[0210] Where Q is the flow rate 19mL / min, t c is the charging time, m is the mass of the carbon coating on the electrode, F is the Faraday constant 96485C / mol, and I is the input current.

[0211] Examples 1-6

[0212] Add the binder PVA (molecular weight: 25000) into deionized water, stir thoroughly in a 90°C water bath to completely dissolve the binder, add the crosslinking agent glutaric acid, then add activated carbon and conductive agent carbon black (particle size of 9nm, resistivity of 0.5Ω·m), stir thoroughly to evenly mix the activated carbon and conductive agent, and obtain electrode slurry. The mass ratio of activated carbon to solvent is 1:2.5, the mass ratio of activated carbon, conductive agent and binder is 91:5:4, and the molar ratio of crosslinking agent to binder is 0.2:1.

[0213] The scraper thickness was adjusted to 450 μm, and the electrode slurry was evenly coated on the graphite paper current collector, and then placed in an oven and dried at 120° C. for 12 hours to obtain a capacitor deionization electrode.

[0214] Except for the different activated carbon used in Examples 1-6, the other conditions are the same. The activated carbon used in Examples 1-6 is listed in Table 1. The adsorption capacity (SAC) and charge efficiency (CE) of the electrodes obtained in Examples 1-6 were tested according to the above method and with a 2000 mg / L NaCl solution. The results are shown in Tables 1 and Figure 3 shown.

[0215] Table 1

[0216]

[0217] Examples 7-10

[0218] Add PVDF (molecular weight: 200000) as a binder to NMP, stir thoroughly to dissolve the binder completely; add petroleum coke activated carbon and conductive agent in Example 1, stir thoroughly to evenly mix the activated carbon and conductive agent therein, and obtain electrode slurry. The mass ratio of activated carbon to solvent is 1:3.5, and the mass ratio of activated carbon, conductive agent and binder is 92:5:3.

[0219] The scraper thickness was adjusted to 450 μm, and the electrode slurry was evenly coated on the graphite paper current collector, and then placed in an oven and dried at 90° C. for 12 hours to obtain a capacitor deionization electrode.

[0220] Except for the different conductive agents used in Examples 7-10, the other conditions are the same. The conductive agents used in Examples 7-10 are listed in Table 2. The adsorption capacity and charging efficiency of the electrodes obtained in Examples 7-10 were tested according to the aforementioned method and using a 2000 mg / L NaCl solution. The results are shown in Table 2.

[0221] Table 2

[0222]

[0223] Examples 11-15

[0224] Add PVDF (molecular weight: 200000) as a binder to NMP, stir thoroughly to dissolve the binder completely in the organic solvent. Add the petroleum coke activated carbon of Example 1 and the carbon black conductive agent of Example 7, stir thoroughly to evenly mix the activated carbon and the conductive agent, and obtain an electrode slurry. The mass ratio of the activated carbon to the solvent is 1:3.5.

[0225] The scraper thickness was adjusted to 450 μm, and the electrode slurry was evenly coated on the graphite paper current collector, and then placed in an oven and dried at 90° C. for 12 hours to obtain a capacitor deionization electrode.

[0226] In Examples 11-15, except that the amount of PVDF used was 2%, 3%, 4%, 6%, and 10% (i.e., the mass ratios of activated carbon, conductive agent, and binder were 93:5:2, 92:5:3, 91:5:4, 89:5:6, and 85:5:10, respectively), the other conditions were the same. The adsorption capacity and charging efficiency of the electrodes obtained in Examples 11-15 were tested in accordance with the aforementioned method using a 2000 mg / L NaCl solution. The results are as follows: Figure 4 shown.

[0227] Examples 16-21

[0228] Add the binder PVDF (molecular weight: 200000) to NMP, stir thoroughly to make the binder completely dissolved in the organic solvent. Add the petroleum coke activated carbon of Example 1 and the carbon black conductive agent of Example 7, stir thoroughly to make the activated carbon and the conductive agent uniformly mixed therein, and obtain an electrode slurry. Among them, the mass ratio of the activated carbon solvent is 1:3.5, and the mass ratio of the activated carbon, the conductive agent and the binder is 92:5:3.

[0229] The electrode slurry was evenly coated on the graphite paper current collector using a scraper, and then placed in an oven and dried at 90° C. for 12 hours to obtain capacitor deionization electrodes of different thicknesses.

[0230] In Examples 16-21, except that the thickness of the scraper was adjusted to 350 μm, 450 μm, 600 μm, 800 μm, 900 μm and 1000 μm, the other conditions were the same. The changes in the electrode thickness of the electrodes prepared in Examples 16-21 before and after drying are shown in Table 3. The adsorption capacity and charging efficiency of the electrodes obtained in Examples 16-21 were tested in accordance with the aforementioned method using a 2000 mg / L NaCl solution. The results are shown in Table 3. Figure 5 shown.

[0231] Table 3. Changes in electrode thickness before and after drying

[0232] <![CDATA[Before drying (μm) * > <![CDATA[After drying (μm) * > % (after drying / before drying) <![CDATA[Carbon loading (g / m 2 )]]> Example 16 350 283 80.86 0.085 Embodiment 17 450 367 81.56 0.120 Embodiment 18 600 493 82.17 0.126 Embodiment 19 800 585 73.13 0.187 Embodiment 20 900 650 72.22 0.239 Embodiment 21 1000 792 79.20 0.322

[0233] * This thickness includes the current collector thickness (200μm)

[0234] Examples 22-25

[0235] Add the binder PVA into deionized water, stir it thoroughly in a water bath at 90°C to completely dissolve the binder; add the crosslinking agent glutaric acid; then add the petroleum coke activated carbon in Example 1 and the carbon black conductive agent in Example 7, stir it thoroughly to evenly mix the activated carbon and the conductive agent, and obtain an electrode slurry. The mass ratio of the activated carbon solvent is 1:2.5, the mass ratio of the activated carbon, the conductive agent and the binder is 91:5:4, and the molar ratio of the crosslinking agent to the binder is 0.2:1.

[0236] The scraper thickness was adjusted to 450 μm, and the electrode slurry was evenly coated on the graphite paper current collector, and then placed in an oven and dried at 120° C. for 12 hours to obtain a capacitor deionization electrode.

[0237] The conditions of Examples 22-25 were the same except that the molecular weight of the binder PVA used was 25000, 47000, 67000, and 195000, respectively. The adsorption capacity and charging efficiency of the electrodes obtained in Examples 22-25 were tested using a 2000 mg / L NaCl solution according to the above method. The results are as follows: Figure 6 shown.

[0238] Examples 26-29

[0239] Add the binder PVA (molecular weight: 25000) into deionized water, stir thoroughly in a water bath at 90°C to completely dissolve the binder; add the crosslinking agent glutaric acid; add the petroleum coke activated carbon of Example 1 and the carbon black conductive agent of Example 7, stir thoroughly to uniformly mix the activated carbon and the conductive agent, and obtain an electrode slurry. The mass ratio of the activated carbon solvent is 1:2.5, and the mass ratio of the activated carbon, the conductive agent and the binder is 91:5:4.

[0240] The scraper thickness was adjusted to 450 μm, and the electrode slurry was evenly coated on the graphite paper current collector, and then placed in an oven and dried at 120° C. for 12 hours to obtain a capacitor deionization electrode.

[0241] Except that the molar ratios of the crosslinking agent to the binder used in Examples 26-29 were 0.05, 0.1, 0.2, and 0.4, respectively, the other conditions were the same. The adsorption capacity and charging efficiency of the electrodes obtained in Examples 26-29 were tested in accordance with the aforementioned method using a 2000 mg / L NaCl solution. The results are shown in FIG. Figure 7 shown.

[0242] Embodiment 30

[0243] Add the binder PVA (molecular weight: 25000) into deionized water, stir thoroughly in a water bath at 90°C to completely dissolve the binder; add the crosslinking agent glutaric acid; add the petroleum coke activated carbon of Example 1 and the carbon black conductive agent of Example 7, stir thoroughly to uniformly mix the activated carbon and the conductive agent, and obtain an electrode slurry. The mass ratio of the activated carbon solvent is 1:2.5, the mass ratio of the activated carbon, the conductive agent and the binder is 92:5:3, and the molar ratio of the crosslinking agent and the binder is 0.2:1.

[0244] The scraper thickness was adjusted to 450 μm, and the electrode slurry was evenly coated on the graphite paper current collector, and then placed in an oven and dried at 120° C. for 12 hours to obtain a capacitor deionization electrode.

[0245] According to the above method, Example 17 (PVDF) and Example 30 (PVA) were tested with a 1000 mg / L NaCl solution. The adsorption capacity and charging efficiency of the obtained electrodes are as follows: Figure 8 shown.

[0246] Examples 31-33

[0247] Add the binder PVA (molecular weight: 25000) into 25 ml of deionized water, stir thoroughly in a water bath at 90°C to completely dissolve the binder; add the crosslinking agent glutaric acid and the non-polymer electrolyte thickener; add the petroleum coke activated carbon of Example 1 and the carbon black conductive agent of Example 7, stir thoroughly to uniformly mix the activated carbon and the conductive agent, and obtain an electrode slurry. The mass ratio of the activated carbon solvent to the solvent is 1:2.5, the mass ratio of the activated carbon, the conductive agent, the binder and the thickener is 89.3:4.7:3:3, and the molar ratio of the crosslinking agent to the binder is 0.2:1.

[0248] The scraper thickness was adjusted to 450 μm, and the electrode slurry was evenly coated on the graphite paper current collector, and then placed in an oven and dried at 120° C. for 12 hours to obtain a capacitor deionization electrode.

[0249] Except that the thickeners used in Examples 31-33 are sodium alginate (AIg), sodium carboxymethyl cellulose (CMC) and polyacrylamide (PAM), the other conditions are the same. The adsorption capacity and charging efficiency of the electrodes obtained in Examples 31-33 and Example 30 were tested according to the above method and with a 1000 mg / L NaCl solution. The results are as follows: Fig. 9 shown.

[0250] Embodiment 34

[0251] Add the binder PVA (molecular weight: 25000) to deionized water, stir thoroughly in a water bath at 90°C to completely dissolve the binder; add the crosslinking agent glutaric acid; add the polymer electrolyte thickener polyethyleneimine and polyacrylic acid to the positive electrode slurry and the negative electrode slurry respectively. Add the petroleum coke activated carbon of Example 1 and the conductive agent carbon black of Example 7 to the positive electrode slurry, wherein the mass ratio of activated carbon to solvent in the positive electrode slurry is 1:2.5, the mass ratio of activated carbon, conductive agent, binder and thickener is 86.5:4.5:3:6, and the molar ratio of crosslinker to binder is 0.2:1. Add the petroleum coke activated carbon of Example 1 and the conductive agent carbon black of Example 7 to the negative electrode slurry, wherein the mass ratio of activated carbon to solvent in the negative electrode slurry is 1:2.5, the mass ratio of activated carbon, conductive agent, binder and thickener is 82.7:4.3:3:10, and the molar ratio of crosslinker to binder is 0.2:1. Stir thoroughly to evenly mix the activated carbon and the conductive agent to obtain positive electrode slurry and negative electrode slurry. Adjust the scraper thickness to 450 μm, and evenly apply the positive electrode slurry and negative electrode slurry on the graphite paper current collector. Place in an oven and dry at 120°C for 12 hours to obtain the capacitor deionization positive electrode and negative electrode.

[0252] The electrodes of Example 34 (PEI & PAA) and Example 30 (without thickener) were tested according to the aforementioned method using a 1000 mg / L NaCl solution. The adsorption capacity and charging efficiency of the obtained electrodes are as follows: Fig.10 shown.

[0253] Examples 35-39

[0254] Examples 35-39 are the same as Example 34 except that the scraper thickness is adjusted differently.

[0255] The changes in electrode thickness of the electrodes prepared in Examples 34-39 before and after drying are shown in Table 4. The adsorption capacity and charging efficiency of the electrodes obtained in Examples 34-39 were tested in accordance with the aforementioned method using a 1000 mg / L sodium chloride solution. The results are shown in Table 4. Fig.11 shown.

[0256] Table 4. Changes in electrode thickness before and after drying

[0257] Before drying (μm)* <![CDATA[After drying (μm) * > % (after drying / before drying) <![CDATA[Carbon loading (g / m 2 )]]> Embodiment 34 450 383 85.11 127 Embodiment 35 650 525 80.77 151 Embodiment 36 850 656 77.18 215 Embodiment 37 900 693 77.00 234 Embodiment 38 1000 782 78.20 303 Embodiment 39 1100 879 79.91 366

[0258] * This thickness includes the current collector thickness (200μm)

[0259] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A method for preparing a capacitive deionization electrode, comprising: Mixing raw materials including activated carbon, a conductive agent, a hydrophilic binder and a solvent to obtain an electrode slurry; The electrode slurry is coated on the surface of the current collector, and after drying, the capacitor deionization electrode is prepared; The mass ratio of the activated carbon to the solvent is greater than 0.2, Wherein, the hydrophilic binder is polyvinyl alcohol, The raw material further comprises a thickener, and the thickener is polyethyleneimine and polyacrylic acid.

2. The method according to claim 1, characterized in that The specific surface area of ​​the activated carbon is 800-2100 m 2 / g.

3. The method according to claim 1, characterized in that The particle size of the activated carbon is 1-15 μm.

4. The method according to claim 1, characterized in that: The average pore size of the activated carbon is 0.5-10 nm.

5. The method according to any one of claims 1 to 4, characterized in that The activated carbon includes one or more of wood activated carbon, fruit shell activated carbon, coconut shell activated carbon and petroleum coke activated carbon.

6. The method according to any one of claims 1 to 4, characterized in that The mass ratio of the conductive agent to the activated carbon is (2-10): (75-96).

7. The method according to any one of claims 1 to 4, characterized in that The particle size of the conductive agent is 8-15 nm.

8. The method according to any one of claims 1 to 4, characterized in that The resistivity of the conductive agent is 0.05-1.50 Ωm.

9. The method according to any one of claims 1 to 4, characterized in that The conductive agent includes one or more of carbon black, acetylene black, carbon nanotubes and graphite.

10. The method according to any one of claims 1 to 4, characterized in that The mass ratio of the hydrophilic binder to the activated carbon is (2-10): (75-96).

11. The method according to claim 10, characterized in that The molecular weight of the hydrophilic binder is 25000-205000.

12. The method according to any one of claims 1 to 4, characterized in that The mass ratio of the thickener to the activated carbon is (1-15):(75-96).

13. The method according to any one of claims 1 to 4, characterized in that The feedstock also includes a cross-linking agent.

14. The method according to claim 13, characterized in that The molar ratio of the crosslinking agent to the hydrophilic binder is (0.05-0.4):

1.

15. The method according to claim 13, characterized in that The cross-linking agent includes one or more of glutaric acid, pentanediol and polyvinyl butyral.

16. The method according to any one of claims 1 to 4, characterized in that The solvent includes an organic solvent and / or an inorganic solvent.

17. The method according to claim 16, characterized in that The solvent includes one or more of 1-methyl-2-pyrrolidone, dimethylacetamide, ethanol, water and acetic acid.

18. The method according to any one of claims 1 to 4, characterized in that The method comprises the following steps: dissolving the hydrophilic binder in the solvent; adding a thickener and optionally a cross-linking agent; Adding the activated carbon and the conductive agent, and mixing to obtain the electrode slurry; The electrode slurry is coated on the surface of the current collector and dried to prepare the capacitor deionization electrode.

19. A capacitive deionization electrode, prepared by the method according to any one of claims 1 to 18.

20. The capacitive deionization electrode according to claim 19, characterized in that: The invention comprises a current collector and an active layer coated on the surface of the current collector, wherein the active layer comprises activated carbon, a conductive agent, a hydrophilic binder and a thickener.

21. The capacitive deionization electrode according to claim 19, characterized in that: The invention comprises a current collector and an active layer coated on the surface of the current collector, wherein the active layer comprises activated carbon, a conductive agent, a cross-linked hydrophilic binder and a thickener.

22. A capacitive deionization reactor comprising the capacitive deionization electrode according to any one of claims 19 to 21.

23. A method for treating water, comprising treating water using the capacitive deionization electrode according to any one of claims 19 to 21 or the capacitive deionization reactor according to claim 22.

24. The water treatment method according to claim 23, wherein the water treatment comprises seawater desalination, wastewater purification, high-purity water preparation, industrial and agricultural water desalination or domestic water desalination.

Citation Information

Patent Citations

  • Preparation method of porous carbon electrode

    CN106783212A

  • Lithium ion battery negative electrode slurry, preparation method, negative electrode piece and battery

    CN110993884A

  • Carbon anode based on positively charged crosslinked chitosan and asymmetric CDI module containing carbon anode

    CN112875813A